Disclosure on Investment Account by Islamic Financial Institutions (IFIs) in Malaysia: Gaps between Malaysia Standards and AAOIFI Standards - Muhammad Iqmal Hisham Kamaruddin; Mustafa Mohd Hanefah; Zurina Shafii (USIM Press, 2024)
Shariah Governance and Assurance in Islamic Financial Sectors (pp. 146-176). Negeri Sembilan: USIM Press, 2019